Informal reasoning regarding socioscientific issues: A critical review of research - Sadler, Troy D. (Journal of Research in Science Teaching, 2004)
Socioscientific issues encompass social dilemmas with conceptual or technological links to science. The process of resolving these issues is best characterized by informal reasoning which describes the generation and evaluation of positions in response to complex situations. This article presents a critical review of research related to informal reasoning regarding socioscientific issues. The findings reviewed address (a) socioscientific argumentation; (b) relationships between nature of science conceptualizations and socioscientific decision making; (c) the evaluation of information pertaining to socioscientific issues, including student ideas about what counts as evidence; and (d) the influence of an individual's conceptual understanding on his or her informal reasoning. This synthesis of the current state of socioscientific issue research provides a comprehensive framework from which future research can be motivated and decisions about the design and implementation of socioscientific curricula can be made. The implications for future research and classroom applications are discussed. © 2004 Wiley Periodicals, Inc. J Res Sci Teach 41: 513–536, 2004